Weekend Effect On Hibor: Test Of A Structural Change - Y. N. Tang, Gordon; S. C. Mak, Billy (Asian Academy of Management (AAM), 1996)
Seasonality has been one of the popular issues in the finance literature. Fama (1965) is one of the earlier researchers who reported seasonality in stock markets. Using the US data, Fama found that the variance on Monday is greater than that for other days. Cross (1973) also showed that negative Monday returns exist in the US stock market. French (1980), Keim and Stambaugh (1984), and Cornell (1985) provided recent evidences on seasonality on stock markets.